2016
DOI: 10.1038/srep19767
|View full text |Cite
|
Sign up to set email alerts
|

Explosive Contagion in Networks

Abstract: The spread of social phenomena such as behaviors, ideas or products is an ubiquitous but remarkably complex phenomenon. A successful avenue to study the spread of social phenomena relies on epidemic models by establishing analogies between the transmission of social phenomena and infectious diseases. Such models typically assume simple social interactions restricted to pairs of individuals; effects of the context are often neglected. Here we show that local synergistic effects associated with acquaintances of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 43 publications
3
52
2
1
Order By: Relevance
“…• In edge-centric approaches, one still considers the transmission channel from infected nodei to susceptible nodej. Now, however, the transmission rate w  i j is affected by the neighborhoods ofi and/orj (for specific examples, see [28,29,44]). Considering only nearest-neighbors, the transmission rate from nodei to nodej at timet, w  ( | ( ) ( )) t z t z t ,…”
Section: Appendix a Non-markovian Gillespie Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…• In edge-centric approaches, one still considers the transmission channel from infected nodei to susceptible nodej. Now, however, the transmission rate w  i j is affected by the neighborhoods ofi and/orj (for specific examples, see [28,29,44]). Considering only nearest-neighbors, the transmission rate from nodei to nodej at timet, w  ( | ( ) ( )) t z t z t ,…”
Section: Appendix a Non-markovian Gillespie Algorithmmentioning
confidence: 99%
“…Conversely, a plethora of complex contagion schemes has been proposed to mediate the assumption of independent transmissions. Examples include correlated, nonlinear transmission channels [26,27], extended neighborhood effects [28,29], and deterministic threshold models [30,31]. So far, not much research has focused on tackling both assumptions simultaneously, and little is know about how these two features interact.…”
Section: Introductionmentioning
confidence: 99%
“…Results are fruitful. For instance, the spreading on complex networks is found to undergo a second-order phase transition in most cases but could be explosive in synergistic epidemics89, and the critical infection probability can be estimated by the mean-field theory10. The networks with heterogeneous degree distribution in general have a lower critical infection probability than those with homogeneous degree distribution11.…”
mentioning
confidence: 99%
“…A recently developed model [29] provides a flexible framework to study any degree of constructive or interfering synergy in any type of network. With this model, it was shown that synergy affects the size, duration and foraging strategy of spreaders [29,32] and can even result in explosive invasions [37] of epidemics with and without node removal and for the Maki-Thompson model [38] describing social phenomena. For regular lattice models, it was found that synergistic effects on invasion are enhanced by increasing local connectivity [32].…”
Section: Introductionmentioning
confidence: 99%